Evaluación de la incorporación de Lactobacillus brevis encapsulado en el alimento sobre los parámetros productivos, salud de pollos Cobb 500 - Mero Ostaiza, Aura Michelle (2019)
The research consisted of evaluating three different doses in dilution of encapsulated Lactobacillus brevis (Lb) administered in the diet of the birds to evaluate the response in productive parameters and health in Cobb 500 chickens. 192 chickens distributed in 4 treatments were used: T0 control, T1 Lb 10-6; T2 Lb 10-7; T3 Lb 10-8 and 3 repetitions. A completely randomized design (DCA) was used and the data was analyzed by ANOVA, the normal distribution of the data (Shapiro-Wilks Test) and homogeneity of variances (Fisher Test), the Tukey test was applied for comparisons of mean (P <0.05). Statistical software was used (Infostat, 2018). Among the productive parameters, significant differences were observed in the weekly weight from the first to the fifth week (P> 0.01) in Q0 (1741.04 g), the results changed in week six in Q3 (2602.42 g). Cumulative weekly food consumption was higher (P <0.01) in T1 (5020 g) compared to the other groups. The feed conversion was higher (P <0.01) in the last three weeks in T2 (1.83) of the animal group. In the immunological variables, the weight of the spleen and Fabricio bag was studied, curiously only the Fabricio bag was greater (P <0.01) in T1 (4.73 g) with respect to the other groups. Finally, only pathogenic bacteria were found in the control group. It is concluded that the use of probiotics improves the health of the birds, however it does not increase their final productive performance.